Comparison of SARS-CoV-2 seroconversion in children with chronic diseases with healthy children and adults during the first waves of the COVID-19 pandemic - Levi Hoste; Levi Hoste; Agnieszka Prytula; Jo Dehoorne; Ruth De Bruyne; Stephanie Van Biervliet; Kathleen De Waele; Evelyn Maes; Victoria Bordon; Arnaud Vanlander; Karlien Claes; Johan Vande Walle; et al. (Frontiers in Pediatrics, 2023)
BackgroundInfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is clinically diverse, and children have a low risk of developing severe coronavirus disease 2019 (COVID-19). However, children with chronic diseases have a potentially increased risk.MethodsWe performed a prospective surveillance study with longitudinal serum SARS-CoV-2 anti-nucleocapsid antibody quantification and questionnaires in pediatric tertiary care patients during the first waves of the COVID-19 pandemic (November 2020–September 2021). The results were compared with those of healthy children and adults from the same geographic area.ResultsWe obtained 525 samples from 362 patients (M/F ratio of 1.3:1; median age of 11.1 years) comprising children with immune-suppressive or immune-modulating drugs (32.9%), inborn errors of immunity (23.5%), type 1 diabetes mellitus (15.2%), and rheumatic diseases (11.9%). A total of 51 (9.7%) samples were seropositive among 37/351 children (10.5%). Seropositivity increased from 5.8% in November–December 2020 to 21.6% in July–September 2021. Compared with adults, a longitudinal analysis revealed reduced seroprevalence but similar kinetics as in children from the same country. Demographic or social variables and disease characteristics did not correlate with seropositivity. Being obese and household contact with COVID-19-infected individuals significantly increased the odds of infection. The majority of seropositive patients had mild symptoms (21/37). One-third were asymptomatic and/or unaware of having COVID-19 (10/37). Four patients (4/37) needed hospitalization, with good clinical outcomes.ConclusionsAlthough harboring a chronic disease, we observed a low SARS-CoV-2 incidence in a cohort of pediatric tertiary care patients, comparable with healthy children during the first year of the pandemic. Infection was mostly associated with mild symptoms.